Johannine Social Identity Formation after the Fall of the Jerusalem Temple : Negotiating Identity in Crisis - Porter, Christopher A. (Biblical Interpretation Series, 2022)
In Johannine Social Identity Formation after the Fall of the Jerusalem Temple Christopher Porter reads the Fourth Gospel through the lens of social identity theory as means of reconciling the social dislocation and trauma of the destruction of the Jerusalem temple. Analysing the Fourth Gospel in conversation with other temple-removed texts of Qumran, Philo, and Josephus the gospel's intent to renegotiate cultic life without the temple can be seen. Through this analysis it is argued that the Fourth Gospel primarily functions as an intra-mural Jewish text, attempting to negotiate the formation of a Jesus-follower social identity in direct continuity with earlier Jewish shared social narratives. Finally, this work reviews the Johannine Community as an outcome of the Gospel identity formation.